Effects of alfalfa fermented feed on growth performance, meat quality, and fecal microflora of Taoyuan Black pigs - Zhu, Yongfei; Lei, Xinyu; Zhang, Xiaoya; Wu, Yongmei; Lv, Biguang; Cheng, Xuan; Cheng, Haoqian; Wang, Li; Li, Yinghui; Li, Cong; Zhang, Zhifei; Lin, Qian (Frontiers in Veterinary Science, 2025)
This study investigated the effects of substituting 50% basal diet with alfalfa fermented feed (AFF) on growth performance, meat quality, serum biochemical parameters, and gut microbiota in finishing-phase Taoyuan Black pigs. A total of 120 healthy pigs were randomly assigned to control (basal diet) and AFF groups (50% basal diet + 50% AFF), with 6 replicates per group (10 pigs/replicate). The experiment lasted 42 days. The results showed that, compared to the control group, the AFF group exhibited no significant differences in growth performance (p > 0.05) but had significantly lower serum triglycerides (TG), alanine aminotransferase (ALT), and malondialdehyde (MDA) levels (p < 0.05). In terms of meat quality, the substitution of AFF significantly increased muscle crude protein, energy levels, and the contents of glutamic acid, alanine, isoleucine, lysine, tyrosine, proline, total amino acids (TAA), umami amino acids (DAA), essential amino acids (EAA), and unsaturated fatty acids (UFA) (p < 0.05) while significantly decreasing the 45-min yellowness value (p < 0.05) and markedly reducing saturated fatty acid (SFA) content (p < 0.01). Regarding the gut microbiota, at the phylum level, the relative abundance of Bacteroidetes, Tenericutes, and Actinobacteria in the experimental group increased significantly (p < 0.05), Spirochaetes rose markedly (p < 0.01), and Proteobacteria decreased markedly (p < 0.01). At the genus level, the relative abundance of Treponema, Ruminococcus, and Prevotella increased significantly (p < 0.05). In conclusion, substituting 50% of the basal diet with AFF in late-stage Taoyuan Black pigs maintained growth performance while enhancing meat quality through improved muscle amino acid profiles and unsaturated fatty acid content. Additionally, it improved serum biochemical and antioxidant indicators and the cecal microbiota, promoting the overall health of the finishing pigs.